APPLICATION OF LITERACY CULTURE IN MADRASAH ALIYAH NEGERI LANGKAT DISTRICT - Ganda Wahyudi, Wahyudin Nur Nasution, Afrahul Fadhila Daulay (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2019)
Abstract: This study aims to determine: (1) an understanding of literacy culture, (2) the application of literacy culture and (3) supporting and inhibiting factors of the application of literacy culture in Madrasa Aliyah Negeri Langkat Regency. Methodologically this research is a qualitative study by seeking, analyzing and making interpretations of data found through document studies, interviews and observations. The data that has been collected is checked for validity through data validity standards in the form of trustworthiness. Data analysis technique is to reduce, present and make conclusions on the results of research. The results of this study are three, namely: First, residents of Madrasa Aliyah Negeri throughout Langkat Regency understand that literacy culture is not just a culture of reading and writing, but also a culture of observing phenomena that develop in society. They see the activities of membaxca, writing and observing the reality that develops in society as an inseparable whole. Second, the strategies of residents of Madrasah Aliyah Negeri in Langkat District in implementing the GLS program include: a) Providing good library facilities; b) Updating the library book collection; c) Require students to borrow 1 book every week; d) Organization of writing competitions; e) Making wall magazines in each subject; and f) Parents of students participate in providing book facilities for students. Third, supporting factors for the implementation of the GLS program at MAN 1 Langkat include: awareness of school residents regarding the importance of literacy culture; adequate physical facilities such as a library, up to date book collection, reading corner etc. ; active participation of madrasa residents; Madrasah budget allocation for the procurement of supporting facilities; the number of posters, bulletin boards, slogans supporting literacy culture in the school environment; many literacy culture activities or events, such as competitions, book donations etc. and the participation of parents or guardians of students. While the inhibiting factors include: there is no specific time for reading books in the classroom; library location which is not ideal yet; not all teachers can accompany students when reading time activities and not all teachers have a good literacy culture.Keywor d:  Appl i c at i on,  Cul t ur e and Madr as ah